What does the Teatro Experimental de Cali tell us today? (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In this interview with Jacqueline Vidal, director of Teatro Experimental de Cali, we talk about the current inclinations of this Colombian theater group in the Latin American theater scene. The interview is part of a larger project, an attempt to seek an approximation to the group's collective creation methodology, in order to disseminate it here in Brazil and minimize the bibliographic gap we have on the relevant theatrical and pedagogical work developed by Teatro Experimental de Cali (TEC) since 1955 in the city of Cali in Colombia.
Keywords: collective creation; latin american theater; Enrique Buenaventura; Jacqueline Vidal